The costs of accidents in Qatar, Oman and Saudi Arabia construction industry. (2nd October 2021) - Umar, Tariq
Considering the construction projects and the current status of occupational safety in the Gulf Cooperation Council (GCC) region, this article attempts to estimate the costs of accidents in construction. The parameters used in these estimates include the values of the current projects in the three main countries including Qatar, Oman, and Saudi Arabia; and the amount disbursed by the government organisations against injuries, disabilities, and deaths. The total costs of an accident in Oman are estimated at US 415, 620 with an economic burden of US 205.73 million/year. In Saudi Arabia, the costs of an accident are estimated at US 91, 940, while the economic burden of the Saudi economy is estimated at US 261.11 million/year. Similarly, the costs of an accident in the Qatari construction industry stand at US 205, 526. The costs of an accident in these countries are quite higher than the costs in the USA, UK, AUS, and SA.